2018
DOI: 10.3758/s13421-018-0875-8
|View full text |Cite
|
Sign up to set email alerts
|

Intensifying the intensity illusion in judgments of learning: Modality and cue combinations

Abstract: We showed that judgments of learning (JOLs) were not affected by presentation modality in a list-learning task, although the typical font-size and loudness illusions emerged in that large-font visual presentations and loud auditory presentations elicited higher JOLs than their less intense counterparts. Further, when items were presented in both modalities simultaneously, largefont/quiet and small-font/loud items received similar JOLs (and were recalled similarly). Most importantly, when the intensity manipula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
1
11
1
Order By: Relevance
“…However, there were indeed some differences between the CR and recognition data. Recognition was higher in the incongruent conditions but CRs were not, consistent with a view that metamemory may be based on factors other than those factors that influence memory and represent a higher-level process (Peynircioğlu & Tatz, 2018; Rhodes, 2016).…”
Section: Summary and Discussionsupporting
confidence: 72%
“…However, there were indeed some differences between the CR and recognition data. Recognition was higher in the incongruent conditions but CRs were not, consistent with a view that metamemory may be based on factors other than those factors that influence memory and represent a higher-level process (Peynircioğlu & Tatz, 2018; Rhodes, 2016).…”
Section: Summary and Discussionsupporting
confidence: 72%
“…If JOLs are at least partly based on the experience of perceptual fluency, multisensory gains in perceptual responses should be mirrored by similar gains in JOLs. It is generally thought that JOLs involve higher-level, post-perceptual processes (e.g., Peynircioğlu, & Tatz, 2019), but we should note that our prediction holds as long as JOLs are in some way based on the ease of processing sensory information. Thus, showing a pattern consistent with the PIE (i.e., lower JOL responses resulting from some unisensory manipulation increase more from information in a second sensory channel) would suggest that implicit, data-driven processes contribute to JOLs (e.g., Koriat, 1997).…”
mentioning
confidence: 62%
“…It is plausible, then, that the presence of one cue may affect the extent to which another cue is used in metacognition just as in perception. Some recent studies employing multiple cues found that cues in metacognition combined additively rather than interactively (e.g., Peynircioğlu, & Tatz, 2019; Undorf & Bröder, 2020). In contrast, Tatz and Peynircioğlu (2020) found that the font size effect and, separately, a related blur effect were reduced with the presence of backgrounds, indicating that these visual cues combined interactively to influence participants’ JOLs.…”
mentioning
confidence: 99%
“…As per font size, participants rate materials presented in larger font size with higher JOLs (Luna, Albuquerque, & Martín-Luengo, 2019; Rhodes & Castel, 2008; Undorf & Zimdahl, 2019; for a meta-analysis, see Luna et al, 2018). As per sound volume, words presented in louder volume are also rated with higher JOLs (Frank & Kuhlmann, 2017; Peynircioğlu & Tatz, 2019; Rhodes & Castel, 2009). Current knowledge strongly suggests that these results are mostly due to people’s beliefs (Blake & Castel, 2018; Luna, Nogueira, & Albuquerque, 2019; Undorf & Zimdahl, 2019).…”
Section: Does Perceptual Information Affect Confidence Ratings?mentioning
confidence: 99%